European Union Infrastructural Development Programs and Economic Growth in Mogadishu, Somalia - Adan, Zakaria Hassan; ohamoud, Ahmed Madey M (Multidisciplinary Journal of Horseed International University (MJHIU), 2025)
This study investigates the impact of European Union (EU) infrastructural development programs on economic growth in Mogadishu, Somalia. It specifically explores the effects of these programs on economic growth, employment generation, and the effectiveness of governance mechanisms in project implementation. A mixed-methods approach was employed, combining quantitative analysis of economic indicators and project data with qualitative interviews from stakeholders, including local government officials, community members, and EU representatives. Data were collected from various sources, including government reports, EU project evaluations, and surveys. The findings reveal that EU-funded infrastructure projects have significantly contributed to economic growth in Mogadishu, correlating with increased GDP and improved connectivity. Furthermore, infrastructure investment has generated substantial employment opportunities, particularly through construction and vocational training initiatives. The study highlights the importance of effective governance mechanisms, which enhance project efficiency and accountability through capacity building, stakeholder engagement, and transparency measures. While EU infrastructure programs have positively impacted Mogadishu, challenges such as security concerns and potential corruption remain. Recommendations include strengthening local governance, enhancing security measures, promoting transparency, and expanding vocational training to sustain the economic benefits of these projects. This study contributes to the understanding of how international development assistance can effectively foster economic growth and resilience in fragile contexts, providing valuable insights for policymakers and development practitioners.